Pengaruh Influencer Marketing Terhadap Keputusan Pembelian Pada Foodbox Bima - Akhmad Fajar; Muhajirin Muhajirin; Muhammad Yusuf (Sharing: Journal of Islamic Economics Management and Business, 2024)
This research aims to determine the influence of influencer marketing on purchasing decisions at Foodbox Bima. This type of research is associative. The research instrument uses a Likert scale questionnaire. The population used is all consumers who have purchased and consumed food or drinks at the Bima City Foodbox, the exact number of which is unknown. Because the population was not known with certainty, the Cochran formula was used and a sample of 96 people was obtained. The sampling technique was carried out using a purposive method. Data collection techniques in this research are observation, questionnaires and literature study. Data analysis techniques use validity tests, reliability tests, simple linear regression, correlation coefficients, determination tests and t tests. The research results show that there is a significant influence of influencer marketing on purchasing decisions at Foodbox Bima with a strong level of relationship and a magnitude of influence of 48.1%.